2005
DOI: 10.1097/01.ede.0000152116.32580.24
|View full text |Cite
|
Sign up to set email alerts
|

Depression and the Risk of Alzheimer Disease

Abstract: Depression was associated with an increased risk of Alzheimer disease. The odds ratios were lower than generally reported from follow-up studies and are similar to cross-sectional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 32 publications
7
69
0
3
Order By: Relevance
“…Risk increased with increasing age a finding that is consistent with the known decline of genetic risk with increasing age [102]. Other chronic inflammatory diseases, for example, depression [103], atherosclerosis [104], and obesity [105] have a clearer epidemiological basis for being proposed to be risk factors in the development of AD. For all of these risk factors the individual attributable risk is likely to be small [81,103,106].…”
Section: Environmental Factorssupporting
confidence: 66%
“…Risk increased with increasing age a finding that is consistent with the known decline of genetic risk with increasing age [102]. Other chronic inflammatory diseases, for example, depression [103], atherosclerosis [104], and obesity [105] have a clearer epidemiological basis for being proposed to be risk factors in the development of AD. For all of these risk factors the individual attributable risk is likely to be small [81,103,106].…”
Section: Environmental Factorssupporting
confidence: 66%
“…In addition, PET imaging studies revealed that cognitive status in patients with AD is inversely correlated with microglial activation, but not Aβ load. 52,53 Finally, in accordance with the above mentioned genome-wide association studies, 7,8 chronic inflammatory diseases and conditions in humans, including atherosclerosis, obesity, diabetes, depression, and periodontitis, [54][55][56][57][58][59][60] all represent either risk factors for or correlate strongly with the risk of late-onset AD.…”
Section: Inflammation-a Key Playermentioning
confidence: 96%
“…Generally speaking, depression in later life shares some characteristics with frailty which also leads to deficits that change the course of normal aging, such as cognitive impairment (Andersen et al 2005); disability (Bruce 2001), fractures (Whooley et al 1999), pain, isolation (Tavares 2004), mortality (Laursen et al 2007) and frailty. The relationship between frailty and depression among elderly is known but not yet clear.…”
Section: Introductionmentioning
confidence: 99%